2021
DOI: 10.3390/cancers13236145
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in the Regulation of Cancer Immune Response: Effect of miRNAs on Cancer Immunotherapy

Abstract: In the last few decades, carcinogenesis has been extensively explored and substantial research has identified immunogenic involvement in various types of cancers. As a result, immune checkpoint blockers and other immune-based therapies were developed as novel immunotherapeutic strategies. However, despite being a promising therapeutic option, immunotherapy has significant constraints such as a high cost of treatment, unpredictable toxicity, and clinical outcomes. miRNAs are non-coding, small RNAs actively invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 196 publications
(192 reference statements)
0
5
0
Order By: Relevance
“…MiR-9 can suppress the activation of the NLPR3 inflammasome and NF-kB signaling, thereby determining the inhibition of CASP1 expression and the secretion of pro-inflammatory factors (IL-1β and IL-18). The up-regulation of miR-9 is also associated with embryonic lethal abnormal vision-like protein 1 (ELAVL1) regulation, anti-inflammatory mechanisms and the inhibition of pyroptosis cell death [ 126 ].…”
Section: Micrornas Interplay With Tnbc and Nlrp3mentioning
confidence: 99%
“…MiR-9 can suppress the activation of the NLPR3 inflammasome and NF-kB signaling, thereby determining the inhibition of CASP1 expression and the secretion of pro-inflammatory factors (IL-1β and IL-18). The up-regulation of miR-9 is also associated with embryonic lethal abnormal vision-like protein 1 (ELAVL1) regulation, anti-inflammatory mechanisms and the inhibition of pyroptosis cell death [ 126 ].…”
Section: Micrornas Interplay With Tnbc and Nlrp3mentioning
confidence: 99%
“…Since the disorder of microRNAs was first discovered in cancer, it has been studied extensively and uncovered new therapeutic possibilities. MiRNAs can regulate multiple signalling pathways of the immune system and have the advantage of multiple targets ( 117 ). Previous studies have shown that restoration of miR-34 expression can reduce the proliferative potential of CRC cells; thus, miR-34 can be used as a therapeutic drug ( 118 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…miR-29a-30 and miR-21-5p) are dependent on the expression of certain miRNAs [ 34 37 ]. Within tumour cells, miRNAs can regulate antigen processing and presentation by targeting one or more components of the antigen processing machinery and MHC-I molecules [ 38 , 39 ]. Previous research has shown the ability of miR-326 and miR-340 for enhancing T cell infiltration in lung adenocarcinoma and large B cell lymphoma, respectively [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%